The Drosophila ATM ortholog, dATM, mediates the response to ionizing radiation and to spontaneous DNA damage during development. - Song, Y.H.; Mirey, G.; Betson, M.; Haber, D.A.; Settleman, J. (Current Biology, 2004)
Cells of metazoan organisms respond to DNA damage by arresting their cell cycle to repair DNA, or they undergo apoptosis. Two protein kinases, ataxia-telangiectasia mutated (ATM) and ATM and Rad-3 related (ATR), are sensors for DNA damage. In humans, ATM is mutated in patients with ataxia-telangiectasia (A-T), resulting in hypersensitivity to ionizing radiation (IR) and increased cancer susceptibility. Cells from A-T patients exhibit chromosome aberrations and excessive spontaneous apoptosis. We used Drosophila as a model system to study ATM function. Previous studies suggest that mei-41 corresponds to ATM in Drosophila; however, it appears that mei-41 is probably the ATR ortholog. Unlike mei-41 mutants, flies deficient for the true ATM ortholog, dATM, die as pupae or eclose with eye and wing abnormalities. Developing larval discs exhibit substantially increased spontaneous chromosomal telomere fusions and p53-dependent apoptosis. These developmental phenotypes are unique to dATM, and both dATM and mei-41 have temporally distinct roles in G2 arrest after IR. Thus, ATM and ATR orthologs are required for different functions in Drosophila; the developmental defects resulting from absence of dATM suggest an important role in mediating a protective checkpoint against DNA damage arising during normal cell proliferation and differentiation.